Gibocercus Szumik and Biguembia Szumik (Embioptera, Archembiidae): new species and the potentiality of female traits - Szumik, Claudia; Gandolfo, Raquel; Pereyra, Veronica (Zootaxa, 2017)
Two new species of Biguembia Szumik (B. mirador n. sp. and B. troncol n. sp.) and one new species of Gibocercus Szumik (G. podamita n. sp.) from Brazil are described and illustrated. The female of Gibocercus chaco Szumik is described for the first time. Female terminalia of both genera are redefined and redescribed for B. copo, G. chaco and G. beni. Additionally, a cladistic analysis using almost 100 morphological characters was developed. Both genera appear monophyletic and well supported by several synapomorphies. The results also indicate that some species are unjustified and therefore they are synonymized: Gibocercus magnus Ross, 2001 = Gibocercus beni Szumik, 1997; Gibocercus flavipes Ross, 2001 = Gibocercus nanai Szumik, 1997; Gibocercus napoa Ross, 2001 = Gibocercus sandrae Ross, 2001, all new synonymies. The relationships of the new species are discussed as well as the potentiality of female traits.